2020
DOI: 10.1007/s15010-020-01529-x
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-associated in-hospital mortality during the 2017/2018 influenza season: a retrospective multicentre cohort study in central Germany

Abstract: The aim of this retrospective cohort study at eight hospitals in Germany was to specify influenza-associated in-hospital mortality during the 2017/2018 flu season, which was the strongest in Germany in the past 30 years. A total of 1560 patients were included in the study. Overall, in-hospital mortality was 6.7% (n = 103), in patients treated in the intensive care unit (n = 161) mortality was 22.4%. The proportion of deceased patients per hospital was between 0% and 7.0%. Influenza was the immediate cause of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Since Brazil faced a major COVID-19 outbreak, with the health system's collapse and almost 100% occupancy in Brazilian intensive care units (Buss et al, 2021 ; Naveca et al, 2021 ; Sabino et al, 2021 ; Silva and Pena, 2021 ), perhaps the attending doctors reserved the few remaining intensive care unit beds for those with confirmed COVID-19 diagnoses. Furthermore, we observed the mortality of those with SARI due to an undefined etiological agent to be lower if compared to SARI due to COVID-19, which is similar to the literature, in which the hospitalized patients with COVID-19 accounted for nearly 37% of lethality rate and hospitalized Influenza patients for only 6.7% of lethality rate (Rößler et al, 2021 ; Zeiser et al, 2022 ). Importantly, in Brazil, the severe SARI cases were more tested than other patients (Boschiero et al, 2021a , b ), which could be associated with a low number of deaths among the patients with SARI due to an undefined etiological agent.…”
Section: Discussionsupporting
confidence: 89%
“…Since Brazil faced a major COVID-19 outbreak, with the health system's collapse and almost 100% occupancy in Brazilian intensive care units (Buss et al, 2021 ; Naveca et al, 2021 ; Sabino et al, 2021 ; Silva and Pena, 2021 ), perhaps the attending doctors reserved the few remaining intensive care unit beds for those with confirmed COVID-19 diagnoses. Furthermore, we observed the mortality of those with SARI due to an undefined etiological agent to be lower if compared to SARI due to COVID-19, which is similar to the literature, in which the hospitalized patients with COVID-19 accounted for nearly 37% of lethality rate and hospitalized Influenza patients for only 6.7% of lethality rate (Rößler et al, 2021 ; Zeiser et al, 2022 ). Importantly, in Brazil, the severe SARI cases were more tested than other patients (Boschiero et al, 2021a , b ), which could be associated with a low number of deaths among the patients with SARI due to an undefined etiological agent.…”
Section: Discussionsupporting
confidence: 89%
“…The overall mortality rate was 6.0% in all 182 adult patients, the in-hospital mortality was 7.6% of 145 hospitalized adults. This rate corresponds to the in-hospital mortality rate of 6.7% out of 1539 influenza patients hospitalized in eight hospitals in central Germany during the influenza season 2017–2018 [ 10 ] and the in-hospital mortality rate of 8.2% out of 195 hospitalized patients in an Austrian tertiary care hospital [ 11 ]. In a University Hospital in Hamburg, the in-hospital mortality was 12.8%; this was due to a high percentage of referred patients from other hospitals for extracorporeal membrane oxygenation (ECMO) treatment [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate in our study is similar to that reported from the others, 0.4%-6.7%. 1,[26][27][28] Most of the severe cases were elderly aged and had comorbidities. 27,28 There are some limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza is a respiratory virus that is highly contagious and easily spreads from person to person by droplet transmission. 1 , 2 , 3 It can involve multiple organ systems such as respiratory tract, cardiovascular, and musculoskeletal, leading to morbidity and mortality. 1 , 2 , 3 Accordingly, there is a high number of influenza cases in Thailand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation